1992
DOI: 10.1029/91ja02379
|View full text |Cite
|
Sign up to set email alerts
|

Parametric excitation of electrostatic whistler waves by electron plasma waves

Abstract: Parametric decay instability of the electron plasma wave into another electron plasma wave and an electrostatic whistler wave has been studied taking into account the full matrix elements. The relevance of this decay channel to the generation of whistler mode radiations in the Spacelab 2 experiment has been pointed out,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These mechanisms can't explain the frequencies and oblique propagation seen in the STEREO data in Breneman et al or in this study. Several studies of correlated Langmuir waves and whistler-mode waves (Kennel et al, 1980;Kellogg et al,1992;Sharma et al, 1992;Ergun et al, 1998)have suggested that either both modes are destabilized by an electron bump-on-tail, or that they may be related by a three-wave decay.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms can't explain the frequencies and oblique propagation seen in the STEREO data in Breneman et al or in this study. Several studies of correlated Langmuir waves and whistler-mode waves (Kennel et al, 1980;Kellogg et al,1992;Sharma et al, 1992;Ergun et al, 1998)have suggested that either both modes are destabilized by an electron bump-on-tail, or that they may be related by a three-wave decay.…”
Section: Introductionmentioning
confidence: 99%
“…They propose that these multiple oblique Langmuir modes of different frequencies combine to produce the modulations. This mechanism has gained wide acceptance, and it is usually proposed that the multiple modes are generated through wave‐wave interactions such as decay of a parent Langmuir wave into an oblique Langmuir wave and a VLF wave that might or might not be observable [ Ergun et al , 1991; Sharma et al , 1992; Newman et al , 1994b; Stasiewicz et al , 1996; Bonnell et al , 1997; Lizunov et al , 2001; Khotyaintsev et al , 2001]. Ergun et al [1991] interpret VLF modulations of auroral Langmuir waves as evidence for a transverse modulational instability (MI) resonant with lower hybrid or ion Bernstein modes.…”
Section: Introductionmentioning
confidence: 99%
“… Lizunov et al [2001] present a full dynamical theory of parametric decay of Langmuir waves into oblique Langmuir and lower hybrid waves in the auroral ionospheric context; Umeda and Ito [2008] present simulations interpreted as decay into Langmuir and ion acoustic waves. Other papers discuss Langmuir wave decay into ion acoustic/lower hybrid/whistler waves in other environments such as solar wind and laboratory plasmas [e.g., Cairns and Melrose , 1985; Cairns and Robinson , 1992; Kellogg et al , 1992; Rizzato and Chian , 1992; Sharma et al , 1992]. In particular, it has been shown convincingly that three‐wave decay plays a role in turbulence in the Earth's foreshock [ Robinson and Cairns , 1995; Bale et al , 1996; Kellogg et al , 1999a, 1999b].…”
Section: Introductionmentioning
confidence: 99%